De la revue d’avant-garde à la reconnaissance publique : la collaboration entre architectes et plasticiens à Liège dans les années 1930 - Sébastien Charlier (In Situ)
In 1928, students from the Academy of Fine Arts in Liege founded a journal of architecture and town planning called L’Équerre. Although it was something of a latecomer to international avant-garde movements, the monthly magazine set out with a view of architecture that focused on the connections between architecture and art. From the beginning, L’Équerre was associated with Anthology, a magazine marked by the theories of Futurism that published artists of the local avant-garde scene. Starting out in the limited context of magazines and exhibitions, artists and architects then went on to work together on ambitious building projects supported by public money. This article aims look at the roots of this collaboration by examining the theoretical and personal links between the two journals. By focusing on public buildings, our analysis will show what concrete actions artists and architects initiated to respond to architectural commissions taking into account the social, political and economic background of a medium-sized Belgian city before the Second World War.